Organizational Factors as Predictors of Knowledge Management Practices in Federal University Libraries in Nigeria - Ugwu, Cyprian Ifeanyi (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2018)
Objective – University libraries in Nigeria are facing challenges arising from poor funding, increasing user demands, and a competitive information environment. Knowledge management has been accepted by information professionals as a viable management tool, but issues surrounding its application require empirical investigation. The aim of this study is to determine the organizational factors that are correlates and predictors of knowledge management practices in federal university libraries in Nigeria.Methods – The study was based on a correlational research design. Twenty heads of university libraries in Nigeria responded to a structured questionnaire developed by the researcher. The questionnaire was validated by experts and its internal reliability was 0.78 obtained through Cronbach’s alpha procedures. The data collected were analyzed using Mean, Standard Deviation, One-Way ANOVA, Pearson’s Product Moment Correlation Coefficient, and regression analysis.Results – The study found that management support and collaboration were the most significant predictors of knowledge management practices in federal university libraries in Nigeria.  Even though human resources policy and rewards systems had positive correlations with knowledge management practices, their correlation coefficients were not significant.Conclusion – The success of knowledge management in university libraries in Nigeria depends on some contextual factors such as the support given by the management staff and the extent of collaboration among staff.